Length changes of Austrian glaciers in 2021/2022 - Kellerer-Pirklbauer, Andreas; Lieb, Gerhard Karl (PANGAEA, 2023)
Glacier length change data of 89 Austrian glaciers were collected for the period summer/autumn 2021 to summer/autumn 2022 (variable period for each glacier depending on specific measurement dates). The measurements in 2022 have been carried out by 19 different teams led by one or two investigators per team (altogether 24 team leaders). The 89 monitored glaciers are well distributed over the glaciated mountain ranges of the Austrian Alps and consider both small and some of the largest glaciers (up to ca.15 km²; e.g., Pasterze) in Austria. Therefore, this sample is considered to be representative for all present-day glaciers in Austria. The monitored glaciers extend from latitude 46°33'N to 47°30'N and longitude 10°04'E to 13°39' E. The data published here comprise the glacier-length-change results for the glaciological year 2021-2022 and are based on a paper published in the official magazine of the Austrian Alpine Club named Bergauf (https://www.alpenverein.at/bk/bergauf/bergauf2023/Bergauf_2_2023). The collected data are also stored in the database of the World Glacier Monitoring Service (WGMS) in Zurich, Switzerland (https://wgms.ch/). Glacier changes at the 89 glaciers was measured in different ways. First, at 71 glaciers the position of the terminus was quantified for 2022 by measuring the distance between distinct marked points in the proglacial area and the ice margin in clearly defined directions (azimuths) for both years. The difference of the measured distances in 2021 and 2022 yields the glacier length change for one specific point. By calculating the arithmetic mean of several of such marked points at a given glacier, the glacier change value was obtained for glaciers with more than one marked point. Second, at ten Austrian glaciers the position of the glacier terminus was quantified for 2022 using Global Navigation Satellite System (GNSS) techniques, unmanned aerial systems (UAS/drones), or other geodetic instruments measuring the glacier terminus for both years. Based on these two GNSS/UAS/geodetic data sets, the glacier length change value was calculated for 2021/2022. Third, for eight glaciers the change of the glacier position was qualitatively determined by photograph comparison or two-year glacier length-change data. For three glaciers (Hintereis Ferner, Landeck Kees, Roter Knopf Kees), a two- or three-year value for the glacier retreat was given, as there is no data for 2021. These were not taken into account when calculating the overall mean value. Results of our analysis show that all observed 89 glaciers retreated. For four glaciers it was not possible to quantify glacier change rates for 2021/2022 due to missing data. Monitoring activities were discontinued for one glacier (Bieltal Ferner) due to the lack of a measurable glacier size. The mean value of the glacier retreat rate of the 78 glaciers measured in 2021 and 2022 was 28.7 m/a (compared to 11.0 m/a in the previous year). This is the highest value in the history of the glacier measurement service of the Austrian Alpine Club. The highest retreat value measured was 89.5 m/a at Schlatenkees Glacier, Venedigergruppe (Venediger Mountains). Regarding the wider context of these results: glacier length changes of Austrian Glaciers are measured annually within the framework of a monitoring program of the Austrian Alpine Club. This program is one of the longest glacier monitoring programs and runs since 1891. Regular measurements of length variations in Austria at single glaciers have been started even earlier. Since 1879, glaciological surveys have been carried out almost annually at for instance Pasterze Glacier, Glocknergruppe (Glockner Mountains) representing one of the longest time series of continuous glacier monitoring worldwide. For more details regarding the glacier monitoring program of the Austrian Alpine Club visit https://www.alpenverein.at/portal/museum-archiv/gletschermessdienst/index.php (only in German).
Keywords: Alps; Austria; glacier length; glacier monitoring